2005
DOI: 10.3171/foc.2005.19.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous intraspinal navigation for access to the subarachnoid space: use of another natural conduit for neurosurgical procedures

Abstract: Object The purpose of this paper was to demonstrate the usefulness of various fiberoptic endoscopes for percutaneous intraspinal navigation of the spinal canal, posterior fossa, and ventricular system. Methods Fresh, unembalmed cadavers were used, in which lumbar punctures were made for access to the sub-arachnoid space (in the case of larger [3.8- and 5-mm-diameter] endoscopes, small laminotomies were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Navigating a laser‐fiber‐coupled system to the site of ligamentum flavum hypertrophy within the spinal canal is a fundamental design challenge for a laser‐driven minimally invasive system. However, advances in percutaneous endoscopic navigation of the spinal canal have already been demonstrated using flexible endoscopes introduced through a small opening in the base of the sacrum called the sacral hiatus . Through this access corridor, the spinal canal can be directly and safely entered through no more than a 2–3 mm incision and without the need for muscle or bony removal.…”
Section: Discussionmentioning
confidence: 99%
“…Navigating a laser‐fiber‐coupled system to the site of ligamentum flavum hypertrophy within the spinal canal is a fundamental design challenge for a laser‐driven minimally invasive system. However, advances in percutaneous endoscopic navigation of the spinal canal have already been demonstrated using flexible endoscopes introduced through a small opening in the base of the sacrum called the sacral hiatus . Through this access corridor, the spinal canal can be directly and safely entered through no more than a 2–3 mm incision and without the need for muscle or bony removal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be possible to insert a microrobot at that site and navigate to the brain for intervention, leaving the skull intact. This principle of using percutaneous intraspinal navigation was recently applied in brain surgery through the use of catheters (37).…”
Section: Figurementioning
confidence: 99%
“…With regard to the safe limit in fiberscope diameter, Stefanov et al 18 have reported that in > 100 human cadavers the subarachnoid space seems to be large enough for coaxial exploration from the spinal subarachnoid space through the cerebral aqueduct by using a 3.0-5.0-mm-diameter fiberscope. Fujimoto and colleagues 4 and Purdy et al 13 have also demonstrated that the spinal canal, posterior fossa, and ventricular system can be approached even with 3.8-5.0-mm-diameter fiberscopes and that a stent can be passed across the third ventricle through a lumbar puncture in cadavers. 6 Further improvements based on clinical experience may also allow routine placement of the fiberscope tip at an intended site in the brainstem subarachnoid space.…”
Section: Discussionmentioning
confidence: 99%